Virtual 3D (MUPAI Virtual 3D). - Zapatero Guillén, Daniel (Arte, Individuo y Sociedad, 2011)
Virtual reality is currently considered a first-order resource for education and training. In this regard, artistic education, like other disciplines, is backing into this technology as a tool to overcome obstacles and contribute new ways of visualization and of providing information. And, in this case, the use of this technology presents enormous advantages for museums, especially, the more modest ones, which have few resources to disseminate and show their collections and works. Moreover, they have to resort to ingenious solutions to solve their difficulties. Therefore, the Pedagogic Museum of Children’s Art (MUPAI) backs into this technology to overcome some of the difficulties it encounters and to allow interested spectators to see its works, with great realism, and to visit its facilities anywhere in the world and at any time of the day. Hence, virtual reality unfolds new possibilities in the field of education that were inconceivable only a short time ago.